2018
DOI: 10.1002/sd.1856
|View full text |Cite
|
Sign up to set email alerts
|

Trust, information sharing and uncertainty: An empirical investigation into their impact on sustainability in service supply chains in the United Arab Emirates

Abstract: The idea of sustainability has yet to enjoy its due share in service supply chains. There has been a dearth of literature in this area, predominantly regarding assessing the impact of collaborative attributes on supply chain sustainability. An integrated supply chain model comprising trust, information sharing and uncertainty practices is proposed here to assess their impact on the sustainability of service supply chains in the United Arab Emirates (UAE). The study conducts a comprehensive literature review to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 63 publications
3
31
0
1
Order By: Relevance
“…This study shows that perceived information sharing quality has a significant effect on partnership trust. This research result is consistent with that of Khan et al [60] and Dubey et al [61], who found that information sharing quality is a contributing factor to partnership trust. However, the perceived information sharing quality does not show any significant effect on partnership commitment.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…This study shows that perceived information sharing quality has a significant effect on partnership trust. This research result is consistent with that of Khan et al [60] and Dubey et al [61], who found that information sharing quality is a contributing factor to partnership trust. However, the perceived information sharing quality does not show any significant effect on partnership commitment.…”
Section: Resultssupporting
confidence: 92%
“…According to the commitment-trust theory, timely, relevant, and reliable information can create trust in partnerships [21] because information sharing can break corporate boundaries and provide cooperation, connectivity, and coordination among supply chain partners [59]. In a recent study, Khan et al [60] also found that the quality of information sharing has a significant impact on trust in the service supply chain. In the E-commerce industry, if the quality of information shared from an EDSP is good, the E-commerce enterprise may thus trust more in this express delivery provider.…”
Section: Development Of Hypothesesmentioning
confidence: 99%
“…These three views all facilitate the decision to share information which also fosters greater trust. In line with this, a study by Khan et al (2018) shows that information sharing has a positive and significant impact on trust. Furthermore, the process of accumulating education enables such a person to develop larger and more knowledgeable social networks.…”
Section: Human Capitalmentioning
confidence: 54%
“…(Black and Hartel, 2003;Liu et al, 2011). Although the concept of sustainability has been investigated in manufacturing supply chains, the notion has recently staring gaining attention pertaining to service supply chains (Hussain et al, 2016a;Khan et al, 2018c).…”
Section: Theoretical Frameworktakeholder Theorymentioning
confidence: 99%